Ocorrência da mosca-negra-dos-citros (Aleurocanthus woglumi ashby) (Hemiptera: Aleyrodidae) em Pernambuco - da Silva Monteiro, Bruno; Rodrigues, Karjoene Cassimiro Villar; da Silva, Anderson Gonçalves [UNESP]; Barros, Reginaldo (My University, 2012)
This paper aimed to verify the presence of black-fly of citrus in the state of Pernambuco in Brazil and wordwide. The material with symptoms were collected in the metropolitan area of Recife/PE and subsequently led to the identification in the Insect Biology Laboratory of the Federal Rural University of Pernambuco - UFRPE on February 4, 2011. The samples collected from the branches of citrus and bilocular, found the presence of eggs, nymphs, pupae and adults of Aleurocanthus woglumi, confirming its occurrence in the state of Pernambuco. The presence of blackfly of citrus had been detected in the city in the state of Pernambuco as Timbaúba, Bom Jardim, Macaparana, Axes, Orobo, São Vincent Farrer and Itambé in citrus plants. Before that had a suspect in the Valley Siriji/PE, now it is in the metropolitan area of Recife, therefore we can confirm that the material collected and identified in the metropolitan area of Pernambuco is A. woglumi.
Occurrence of blackfly (Aleurocanthus woglumi ashby) (Hemiptera: Aleyrodidae) in the state of Pernambuco
Keywords: Black fly; Citrus; Pest